2005
DOI: 10.1111/j.1365-2958.2005.04498.x
|View full text |Cite
|
Sign up to set email alerts
|

LmxMPK9, a mitogen‐activated protein kinase homologue affects flagellar length in Leishmania mexicana

Abstract: SummaryComponents of mitogen-activated signal transduction pathways have been shown to be involved in flagellum biogenesis and maintenance. A mitogenactivated protein kinase homologue, designated LmxMPK9 from Leishmania mexicana , has been recently identified in a homology screen and its mRNA found to be present in all life stages. Three different splice-addition sites were used for mRNA maturation in trans -splicing in the different life stages. However, here we show that LmxMPK9 protein is exclusively found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
106
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 34 publications
(45 reference statements)
3
106
1
6
Order By: Relevance
“…DYF-5 encodes a putative MAP kinase that regulates the length of sensory cilia in C. elegans, similar to what has been reported for DYF-5 homologues in Chlamydomonas (LF4) and Leishmania (LmxMPK9) (17,18): dyf-5 loss-of-function results in cilia elongation, whereas overexpression results in shorter cilia. In addition, fluorescence and EM showed that, in the absence of DYF-5, the cilia are more dispersed and that many cilia are not properly aligned into the amphid channel and sometimes turn back to the base, although some cilia do enter the channel.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…DYF-5 encodes a putative MAP kinase that regulates the length of sensory cilia in C. elegans, similar to what has been reported for DYF-5 homologues in Chlamydomonas (LF4) and Leishmania (LmxMPK9) (17,18): dyf-5 loss-of-function results in cilia elongation, whereas overexpression results in shorter cilia. In addition, fluorescence and EM showed that, in the absence of DYF-5, the cilia are more dispersed and that many cilia are not properly aligned into the amphid channel and sometimes turn back to the base, although some cilia do enter the channel.…”
Section: Discussionmentioning
confidence: 72%
“…We wondered whether mutations in dyf-5 affect cilia morphology and length, as in Chlamydomonas and Leishmania (17,18). Visualization of the microtubular axonemes of the cilia using anti-tubulin antibodies revealed that the cilia of dyf-5(lf) animals were not properly aligned into the amphid pore.…”
Section: Mutation Of Dyf-5 Affects Cilia Morphology and Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…LF4 encodes a protein highly similar to mammalian male germ cell-associated kinase (Mak) and intestinal cell kinase (ICK) (13). Loss of function of the LF4 homologs Caenorhabditis elegans dye-filling defective 5 (Dyf-5) and Leishmania Mexicana LmxMPK9 also causes slightly elongated cilia or flagella (14,15). However, molecular regulatory mechanisms controlling ciliary length remain unknown.…”
mentioning
confidence: 99%